1991
DOI: 10.1016/0014-5793(91)80295-e
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of human cystatin C and kininogen by human cathepsin D

Abstract: Inactivation ofhuman eystatin C and kininogen by human cat, hepsin D Univcrslt, v th~sptml, S.221 85 l.und, 3"wcdcn Received i 6 Janultry 1991 A p~p~ln tnltibitor of 22 kDa was isolated from human pt=te=nta and shown to ~ identical to residues Cy~146.keu:t?.~ of the third domain of human klninol~en. This kinino~en dam;tin anti reeon~binan~ hun~an cystatin C were tmtettvated by pcptlde bond eleavalles at hydrophobic amino acid residues due to Ihe etClion of cathepsin D, Tlie~e results ftmher support 11~c pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
53
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(54 citation statements)
references
References 26 publications
1
53
0
Order By: Relevance
“…Thus, cystatins may bind to cathepsin B and limit its extralysosomal functions. Interestingly, human genome does not encode aspartate-specific protease inhibitors, which could antagonize functions of cathepsin D (55); moreover, cathepsin D is able to inactivate cystatins (56,57). Importantly, we found that cathepsin D was secreted earlier than cathepsin B in dsRNAstimulated cells.…”
Section: Discussionmentioning
confidence: 85%
“…Thus, cystatins may bind to cathepsin B and limit its extralysosomal functions. Interestingly, human genome does not encode aspartate-specific protease inhibitors, which could antagonize functions of cathepsin D (55); moreover, cathepsin D is able to inactivate cystatins (56,57). Importantly, we found that cathepsin D was secreted earlier than cathepsin B in dsRNAstimulated cells.…”
Section: Discussionmentioning
confidence: 85%
“…The ECM contains several specific protease inhibitors, including members of the family of tissue inhibitors of metalloprotease [56], plasminogen activator inhibitor [57,58]. cystatin and stefin families [59,60]. The balance between the relative level of proteases and their specific inhibitors dictates the degree of protease activity, and essentially ensures that uncontrolled proteolysis of the components of the basement membrane does not occur.…”
Section: The Integrinsmentioning
confidence: 99%
“…These proteases appear to form a proteolytic cascade that initially degrades the protease inhibitors, abolishing their effects, and subsequently degrades many components of the basement membrane. For example, cathepsin D actively degrades cystatin C, the major inhibitor of cathepsin B, resulting in the enhancement of the enzymatic activity of cathepsin B [59]. which itself activates UPA [68] and degrades collagen type IV, laminin and fibronectin [69].…”
Section: The Integrinsmentioning
confidence: 99%
“…The mechanisms controlling the intracellular inhibition of cysteine proteinases in endosomes and lysosomes with cystatin C entering the endosomal -lysosomal pathway by endocytotic uptake may include dimerisation (Ekiel and Abrahamson, 1996;Merz et al, 1997), proteolytic fragmentation by cathepsin D (Lenarčič et al, 1991) or neutrophilic granulocyte elastase (Abrahamson et al, 1991). Some of these mechanisms may operate already in the pericellular microenvironment and may restrict the inhibitory function of the secreted cystatin C against the proteolytic activity of cell surface associated and/or secreted enzymes (Křepela et al, 1998).…”
mentioning
confidence: 99%